2013
DOI: 10.1057/jibs.2013.34
|View full text |Cite
|
Sign up to set email alerts
|

MNC subsidiary channel relationships as extended links: Implications of global strategies

Abstract: Foreign subsidiaries of multinational corporations (MNCs) rely on external partners, such as channel partners, to achieve global objectives. We conceptualize the subsidiary's channel partner as an extended link of the MNC's internal network: thus, the subsidiary's adaptation and execution of the MNC's global strategies should influence the subsidiary's channel relationship and performance. Building on the strategy-environment alignment framework, we study the influence of MNC global strategies (global efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 123 publications
(182 reference statements)
0
28
0
Order By: Relevance
“…For example, both environmental uncertainty and market dynamism retard the effective coordination and ruin the relationship among the interacting parties (Hada, Grewal, & Chandrashekaran, 2013). They also undermine the willingness to fulfill agreed-upon obligations, as well as cause difficulties in making adjustments that are critical to preserving the relationship (Griffith & Zhao, 2015;Katsikeas et al, 2009).…”
Section: Moderation Hypothesesmentioning
confidence: 99%
“…For example, both environmental uncertainty and market dynamism retard the effective coordination and ruin the relationship among the interacting parties (Hada, Grewal, & Chandrashekaran, 2013). They also undermine the willingness to fulfill agreed-upon obligations, as well as cause difficulties in making adjustments that are critical to preserving the relationship (Griffith & Zhao, 2015;Katsikeas et al, 2009).…”
Section: Moderation Hypothesesmentioning
confidence: 99%
“…This body of work has investigated the importance of various firm, buyer, and market characteristics for the ability of firms to create or enjoy performance outcomes of strong buyer relationships. For example, studies have demonstrated the importance of national culture and cultural distance (Homburg et al 2009; Leonidou et al 2014; Lund, Scheer, and Kozlenkova 2013; Zhou and Xu 2012), psychic distance (Hada, Grewal, and Chandrashekaran 2013; Johnston et al 2012), high- versus low-context communication culture (Jean, Sinkovics, and Kim 2010), and cross-cultural skills (Sichtmann and von Selasinsky 2010) for firms’ abilities to build and benefit from strong buyer relationships. Research has also demonstrated the role of firm status as foreign versus local (Dong, Li, and Tse 2013), firms’ intercountry coordination (Gao and Shi 2011; Shi et al 2010), and the effects of country (Barnes et al 2014; Dyer and Chu 2000; Steward et al 2010).…”
Section: Buyer–seller Relationships In Transition Economiesmentioning
confidence: 99%
“…Considering the market competition and dynamics, if subsidiaries want to have absorptive capacity, the degree of autonomy should be considered by MNEs, which echoes Glaister et al (2003). Subsidiaries' autonomy often depends on market competition and the extent to which they intend to execute the springboard strategy (Hada et al, 2013;He & Wong, 2004). When autonomy exists, subsidiaries are free to make decisions to determine the extent to which they need to absorb external capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…If subsidiaries are regarded as the implementers of the global strategy of MNEs, in order to address this, the enterprise needs the subsidiaries to enact an aggressive integration strategy, and so it needs to fully authorize the subsidiaries' autonomy. Hada et al (2013) pointed out that in order to be able to further grow in the host country, subsidiaries need to have committed relationships with local access partners. This committed relationship comes from the enterprise's globalization strategy, and, more importantly, the decision-making autonomy that establishes access relationships can be achieved.…”
Section: Market Conditions and Autonomy Empowermentmentioning
confidence: 99%
See 1 more Smart Citation